Did early diagnostic confirmation save lives during the COVID-19 pandemic?: Evidence from China - Chen, Simiao; Jin, Zhangfeng; Bärnighausen, Till; Bloom, David E. (China economic review, 2025)
This paper investigates the impact of early diagnostic confirmation on the COVID-19 pandemic in a developing country. Using a dataset of the first laboratory-confirmed cases across Chinese cities and an instrumental variable strategy to address endogeneity, we show that reducing the time to publicly confirm the first case in a city by one day led to reductions of 9.4 % in COVID-19 prevalence and 12.7 % in mortality over the subsequent six months. The impact was more pronounced in cities farther from the COVID-19 epicenter, with lower migration exposure, more responsive public health systems, and lower health system capacity utilization. Enhanced social distancing and a less overstressed health system likely drove these effects. Our findings underscore the importance of allocating resources to improve diagnostic technologies; strengthening public health emergency response systems to test for, diagnose, and announce cases of infection; and acting swiftly when facing a potential outbreak.